Ethics of Criminal Reporting on Women in Online Media: Theo Van Leeuwen Analysis and Islamic Perspective - Mirna; Jumraini; Nadila Kamaruddin (Institut Bahri Asyiq Galis Bangkalan, 2026)
Using Theo Van Leeuwen’s critical discourse analysis model and Islamic perspectives, this study aims to examine the ethics of crime reporting on women in online media. The study focuses on the news coverage of a woman’s murder in Pekanbaru published by Kompas.TV. This research employed a descriptive qualitative method with data collection techniques through documentation, including reading, note-taking, coding, and identifying the representation of social actors within news texts. Data analysis was conducted systematically through the classification of exclusion and inclusion strategies in representing victims, perpetrators, and authorities in the news discourse. The findings reveal that Kompas.TV applies exclusion and inclusion strategies to construct social actors in crime reporting. From an Islamic perspective, news ethics should prioritize the principles of qaulan sadidan and qaulan ma’rufa, while avoiding slander and the exposure of disgrace that may degrade human dignity. The study also indicates that media representations emphasizing victims’ emotional aspects demonstrate that news reporting is not entirely neutral and significantly influences public opinion and social perception.